Penataan Trotoar Jalan Sisingamaraja - Jalan Panglima Polim Jakarta Selatan DKI Jakarta DKI Jakarta - Astuti, Retno Fitri; Akromusyhada, Akhmad; Pratiwi, Feny Ida (Universitas Pelita Bangsa, 2021)
The arrangement of pedestrian paths on Jalan Sisingamangaraja-Jalan Panglima Polim in South Jakarta, DKI Jakarta aims to improve the quality of pedestrian infrastructure and support safer and more comfortable movement. This study examines the existing condition of the sidewalk, identifies existing problems, and formulates a comprehensive and sustainable design solution. The planning approach used involves an analysis of sidewalk width, materials used, support facilities, as well as aspects of safety and accessibility for all users including the disabled. This arrangement plan also considers environmental aesthetics and integration with the surrounding public space. The implementation of this sidewalk arrangement is expected to reduce congestion, improve pedestrian safety, and encourage more people to walk, thus contributing to improving air quality and public health. The conclusion of this study shows that good sidewalk planning not only has a positive effect on mobility, but also on the quality of life of South Jakarta residents as a whole.